2011
DOI: 10.1002/ajmg.b.32015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MECP2 exon 1 in classical rett patients disrupt MECP2_e1 transcription, but not transcription of MECP2_e2

Abstract: The overwhelming majority of Rett syndrome cases are caused by mutations in the gene MECP2. MECP2 has two isoforms, termed MECP2_e1 and MECP2_e2, which differ in their N-terminal amino acid sequences. A growing body of evidence has indicated that MECP2_e1 may be the etiologically relevant isoform in Rett Syndrome based on its expression profile in the brain and because, strikingly, no mutations have been discovered that affect MECP2_e2 exclusively. In this study we sought to characterize four classical Rett pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
(39 reference statements)
1
20
1
Order By: Relevance
“…This contrasts with several previous studies which used quantification of end-point RT-PCR products and showed higher levels of e1 than e2 [2], [3]. Our previous study looking at e1 and e2 mRNA levels in lymphocytes using the ΔΔCt method also showed very similar levels of e1 and e2 [17], also differing from the previous reports [2], [3]. This may not, however, correspond directly to relative amount of the protein isoforms, as e1 is translated with much higher efficiency than e2 [3], and has been shown to be a more stable protein than e2 [10], and as predicted by in silico analysis of the different N-terminal sequences for likelihood of N-methionine excision and N-terminal acetylation and effect on protein stability and longevity [10].…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with several previous studies which used quantification of end-point RT-PCR products and showed higher levels of e1 than e2 [2], [3]. Our previous study looking at e1 and e2 mRNA levels in lymphocytes using the ΔΔCt method also showed very similar levels of e1 and e2 [17], also differing from the previous reports [2], [3]. This may not, however, correspond directly to relative amount of the protein isoforms, as e1 is translated with much higher efficiency than e2 [3], and has been shown to be a more stable protein than e2 [10], and as predicted by in silico analysis of the different N-terminal sequences for likelihood of N-methionine excision and N-terminal acetylation and effect on protein stability and longevity [10].…”
Section: Discussioncontrasting
confidence: 99%
“…5B). The contractile force generated by blue light (~24 mW/mm 2 ) was comparable to that produced by 1 μM phenylephrine (16) a selective α-adrenergic receptor agonist, and even larger than that produced by 60 mM KCl (Fig. 5C, E).…”
Section: Resultsmentioning
confidence: 69%
“…Since the discovery of MeCP2E1 isoform, scientists have started to reevaluate the mutation analysis of exon 1. To date, several RTT-causing mutations are reported within exon 1 encoding for MeCP2E1 (Gianakopoulos et al 2012;Saunders et al 2009;Chunshu et al 2006;Quenard et al 2006;Bartholdi et al 2006;Saxena et al 2006;Ravn et al 2005). Studies conducted in [2005][2006] suggested that mutations in exon 1 are rare in RTT, because they could only detect exon 1 mutations in 0.03-1 % of the tested samples from RTT patients (Amir et al 2005;Quenard et al 2006;Evans et al 2005b).…”
Section: Presence Of Mutations and Relevance To Rttmentioning
confidence: 99%